Mainländer, lector de Spinoza: encuentros y desencuentros con el panteísmo (ALPHA. Journal of Arts, Literature and Philosophy, 2025)
Mainländer’s philosophy is strongly inspired by Schopenhauer’s pessimism. However, he also deeply admired Spinoza for his life and work. This article defends the thesis that Mainländer, despite rejecting pantheism for scientific reasons, inherits fundamental conceptions from Spinoza to his system: the concept of substance, the nature of politics and the suicide of God. To do this: (i) the denial of God in the world is explained as a scientific necessity; (ii) what Mainländer understands by pantheism is described, and; (iii) the influence of Spinoza on Mainländer is analyzed. It is concluded that for a more appropriate understanding of Mainländer’s philosophy, it is necessary to distance him from the shadow of Schopenhauer and consider the various sources that gave rise to his thought.
Keywords: God; Mainländer; Pessimism; Spinoza; Suicide